Humanism as a Category of Religious Alternative - Asuquo, Offiong Offiong (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
Man is faced with several problems in life and issues which disturb and frighten him. There are some other issues of life which he does not understand, for instance, the source of life, the origin of death, the nature of the hereafter. He also desires peace, comfort and security in life. These and several other reasons have made man to search for answers and solutions to his predicament. This search has given rise to the various known religions. However, despite the existence of these religions, man’s problem still persists. This situation has made some people to suggest or advocate the adoption of other secular alternatives to religion, with the hope that they may solve man’s problems. This paper examines one of such secular alternatives called Humanism. In this process, it examines its meaning, and the merits and demerits of some humanistic theories. This is meant to help the reader to decide whether to adopt it or not.